Cross-cultural adaptation and implementation of Good Life with osteoarthritis in Denmark (GLA:D™): group education and exercise for hip and knee osteoarthritis is feasible in Canada. Issue 2 (February 2018) - Davis, A.M.; Kennedy, D.; Wong, R.; Robarts, S.; Skou, S.T.; McGlasson, R.; Li, L.C.; Roos, E.
Summary: Objective: Adapt and evaluate the feasibility of implementing Good Life with osteoArthritis in Denmark (GLA:D TM ) in Canada for people with mild to severe hip/knee osteoarthritis. Methods: Patients triaged to non-surgical management participated in two education sessions and 12 supervised, neuromuscular exercise classes. We used the RE-AIM implementation framework evaluating outcomes of Reach, Effectiveness/Efficacy, Adoption, Implementation and Maintenance. Patients completed surveys pre-program and at 3 months follow-up. Program fidelity was evaluated at four observations against a priori criteria. We conducted semi-structured interviews with therapists post-program. Results: 72 patients consented to participate, 59 started the program and one withdrew on physician advice. The remaining 58 provided follow-up data. Mean age was 67 years; 78% were female and 52% had body mass index (BMI) >25. The effect of the program was demonstrated: 40% improvement in pain with 59% achieving a clinically important improvement of ≥2 points on the Numeric Pain Rating scale. Statistically significant improvement also occurred in the Hip disability/Knee injury and Osteoarthritis Outcome Score subscales. 24% reported increased physical activity. Program fidelity was demonstrated with all criteria met. Therapists emphasized that rolling recruitment allowed appropriate supervision and resulted in participants encouraging each other. 99% of participants indicated they benefitted from and were satisfied with the program and 90% reported using the knowledge daily. 52% were willing to pay >$250 Cdn for the program. Conclusion: GLA:D TM implementation was feasible in the Canadian context with results similar to those of >7, 000 participants in Denmark. Implementation and evaluation of GLA:D TM Canada is now occurring nationally.